Modern PHP: New features and good practices - Lockhart, Josh. (Beijing, China : O'Reilly Media, Incorporated, 2015)
PHP is experiencing a renaissance, though it may be difficult to tell with all of the outdated PHP tutorials online. With this practical guide, you$1 (Bll learn how PHP has become a full-featured, mature language with object-orientation, namespaces, and a growing collection of reusable component libraries.s
LANGUAGE FEATURES. The new PHP -- Features -- GOOD PRACTICES. Standards -- Components -- Good practices -- DEPLOYMENT, TESTING, AND TUNING. Hosting -- Provisioning -- Tuning -- Deployment -- Testing -- Profiling -- HHVM and Hack -- Community
Includes index.
Keywords: PHP (COMPUTER PROGRAM LANGUAGE)